Partnering with Students to Develop a Capstone for a Graduate Health Informatics Program - Jezrawi, Rita; Zahorka Derka, Stephanie; Warnick, Elizabeth; Foley, Jasmine; Patel, Vritti; Pavithran, Neethu; Bernier, Thérèse; Wagner, Nicole; Barr, Neil G.; Maccio, Vincent; Leyland, Margaret; Lokker, Cynthia (Applied Clinical Informatics, 2024)
Objective This study aimed to assess the desirability, feasibility, and sustainability of integrating a project-based capstone course with the course-based curriculum of an interdisciplinary MSc Health Informatics program guided by a student-partnered steering committee and student-centered approach.Methods We conducted an online cross-sectional survey (n = 87) and three semistructured focus groups (n = 18) of health informatics students and alumni. Survey data were analyzed descriptively. Focus groups were audio-recorded and transcribed verbatim and then analyzed using a general inductive and classic analysis approach.Results Most students supported including a capstone project but desired an option to work independently or within a group. Students perceived several benefits to capstone courses while concerned over perceived challenges to capstone implementation, evaluation, and managing group processes. The themes identified were (1) professional development, identity, and career advancement, (2) emulating the real world and learning beyond the classroom, (3) embracing new, full-circle learning, (4) anticipated course structure, delivery, and preparation, (5) balancing student choice, interests, and priorities, and (6) concerns over group dynamics, limitations, and support.Conclusion This study demonstrates the value of having students as partners at each stage in the process from methods conception to course curriculum design. With the steering committee and the curriculum developer, we codeveloped a student-centered course that integrates foundational digital health-related project knowledge acquisition with an inquiry-based project that can be completed independently or in small groups. This study demonstrates the potential benefits and challenges that health informatics educators may consider when (re)designing capstone courses.
Keywords: interdisciplinary education; digital health; health informatics; experiential learning; problem-based learning; students as partners